The Kafala System: Perspective of Middle Eastern Culture and Its Impact on Migrant Workers - Akmalia, Aifa Humaira; Letmiros, Letmiros (Mahesa Research Center, 2025)
This study analyzes the kafala system in the Middle East, which is often regarded as a form of modern slavery against migrant workers. While the system has been examined from various perspectives, this research focuses on the relationship between the kafala system and Middle Eastern culture, as well as the influence of cultural factors on its persistence and implementation in the contemporary era. The study employs a qualitative method with an ethnographic approach based on secondary data, including books, journal articles, and international reports. The theoretical framework used is the Cultural Lag Theory developed by William Ogburn (1922). The analysis reveals that the current kafala system is a combination of traditional Middle Eastern cultural practices and the legacy of British colonialism during the 1970s, which has since evolved over time. Despite widespread international criticism, the system persists due to cultural values in the Middle East that support social hierarchy and control over foreign workers. Various reforms have been implemented to improve the welfare of migrant workers. This study affirms that understanding cultural factors is crucial in formulating a policy analysis basis and diplomatic strategies to strengthen the protection of Indonesian migrant workers.